Antimicrobial Efficacy of Few Commercially Available Herbal and Non Herbal Tooth Pastes Against Clinically Isolated Human Cariogenic Pathogens - Bora, Amitava; Sen, Sharmista; Goswami, Abhirup; Kundu, Gautam Kumar; Ghosh, Biswajit (Bangladesh Journal of Dental Research & Education, 2015)
Objective: The aim of this study was to compare the antimicrobial efficacy of ten commercially available herbal and non herbal toothpastes. Methods: Ten toothpaste brands (A-J) were collected. A, C, D, E contained Herbal components only, toothpastes B, F, G contained herbal components and fluoride as main anticariogenic agent, toothpastes H and I contained fluoride and triclosan combination and toothpaste J contained fluoride only as main anticariogenic component. Dental caries samples were collected from 6-14 years old children having occlusal caries in permanent fully erupted molar teeth involving enamel and dentin but caries not involving dental pulp and Streptococcus mutans bacteria isolated by laboratory method. The antimicrobial activity was assessed by measuring the inhibition zones by agar well diffusion method. Results: Fluoridated toothpaste with triclosan had maximum antimicrobial activity at all concentrations when compared to Herbal toothpaste. Conclusion: Toothpastes containing fluoride and triclosan are most effective but herbal tooth pastes have the prospect of becoming safer and effective altenative and provide an ideal home care anticariogenic regimen. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22454 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 14-18